HOW DOES SOCIAL MEDIA MARKETING INFLUENCES YOUTH CUSTOMERS? A LITERATURE REVIEW - Nur Rafiqah binti Tahir; Milfadzhilah Mohd Jamil; Mariatul Qibtiyah binti Hasloni; Khairun Nisa binti Jumali; Jahlelawati binti Yub Rembeli; Nuramera binti Amir (International Journal of Accounting, Finance and Business, 2022)
The influence of social media is enormous and is the most powerful medium, especially in the field of marketing in the current era of modernization. Numerous methods of social media advertising and marketing can attract consumers of various ages, especially youth. This paper aims at presenting the reviews of the literature on social media influencing the youth consumer. The previous studies give positive feedback on social media as one of the marketing tools to influence the customer and consumer, especially youth. The review will give a holistic understanding of the social media influencing youth and marketing concepts for future researchers and aid to identify the research gap.